KARAKTERISTIK LINGKUNGAN TERHADAP KOMUNITAS SERANGGA (Environmental Characteristics of Insect Community) - Muhammad Rezzafiqrullah Rehan Taradipha (Graduate School Bogor Agricultural University (SPs IPB), 2019)
The poorly managed development of Banyumas Regency causes changes in the quality of the environment. insects can be used as indicators of environmental quality changes. The purpose of this research is to identify the abiotic environmental factors, biotic and potential environmental disturbance to the insect community and to analyze the potential insects as environmental bioindicators. Insect data collection uses four types of traps: pitfall traps, yellowpan traps, sweep net and malaise traps. data analysis is done by linking the relationship between insect community parameters with environmental parameters. The presence of insects at the study site is influenced by plant wealth, airborne TSP concentration, canopy cover, light intensity, and wind speed. The presence of insects correlates with the increasing environmental factors that support life and decreases against environmental disturbances. Digitonthopagus sp., Polyrhachis sp., Eurema sp. 2, Junonia sp., Neptis sp., Papilio sp., Elymnias sp. can be used as an indicator of habitat conditions with low environmental disturbances. Onthophagus sp3., Oreogeton sp., Appias sp., Trilophidia sp. can be used as an indicator of habitat conditions with high environmental disturbances.